PENERAPAN PEMBELAJARAN BERBASIS PEMECAHAN MASALAH DENGAN MENGGUNAKAN PETA KONSEP PADA POKOK BAHASAN SUHU DI SMP NEGERI 3 BANDA ACEH - Siraj Siraj (JURNAL FISIKA EDUKASI, 2014)
The purpose of this study was to determine: 1) Increasing student achievement; 2) Activity of teachers and students; and 3) Skills teachers manage learning through the application of problem based learning using concept maps. Subjects in this study were all students of class VII6 first half SMP Negeri 3 Banda Aceh Academic Year 2008/2009 amounting to 31 people. Objects in this study are problem based learning using a concept map on the material temperature. Data analysis using descriptive statistics and the percentage of mastery learning. Based on the results of research and data analysis can be concluded: 1) The use of problem based learning using concept maps are effective in improving student achievement on the material temperature at SMP Negeri 3 Banda Aceh, this can be seen on an individual basis ranging completeness 85,1%, 85,5% and 86,29%. Completeness in classical ranging 85,08% , 85,48% and 86,29%; 2) the most dominant activity appears teachers are guiding students to make hypotheses, guiding students create concept maps and guide students to discuss. While students most dominant activity is hypothesized appear, make concept maps and discussions; and 3) manage the learning skills of teachers has increased, from the category of good, excellent and good.